Efektifitas Pengeluaran Dana Desa di Desa Kedamean Kecamatan Kedamean Kabupaten Gresik Tahun 2025 - Vicensia Syafila Prayadin; Cindy Aulia Ainur Azizah; Intan Dwi Sukowati; Muhammad Irfan Bahi Haqi; Hanifah Alya Hidayah (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to analyze the effectiveness of village fund expenditure in Kedamean Village, Kedamean District, Gresik Regency in 2025. The approach used is qualitative with descriptive methods, through in-depth interviews with the Village Head, Treasurer, and Village Consultative Body, as well as analysis of official documents such as budget realization reports and Village Budget Work Plans. The results of the study indicate that village fund expenditure in Kedamean Village is classified as very effective which has followed the principles of transparency and accountability according to regulations, but several obstacles are still found such as inconsistencies between planning and implementation, limited capacity of village officials, and less than optimal realization of development programs and community empowerment. This study recommends strengthening the capacity of village officials, increasing community participation, and optimizing internal and external supervision to increase the effectiveness of village fund expenditure in order to achieve sustainable village development and improve community welfare.